Ultrathin ALD Coatings of Zr and V Oxides on Anodic TiO2 Nanotube Layers: Comparison of the Osteoblast Cell Growth - Baishya, Kaushik; Bacova, Jana; Al Chimali, Bachar; Capek, Jan; Michalicka, Jan; Gautier, Gael; Le Borgne, Brice; Rousar, Tomas; Macak, Jan M (ACS applied materials & interfaces, 2025)
The current study investigates and compares the biological effects of ultrathin conformal coatings of zirconium dioxide (ZrO2) and vanadium pentoxide (V2O5) on osteoblastic MG-63 cells grown on TiO2 nanotube layers (TNTs). Coatings were achieved by the atomic layer deposition (ALD) technique. TNTs with average tube diameters of 15, 30, and 100 nm were fabricated on Ti substrates (via electrochemical anodization) and were used as primary substrates for the study. The MG-63 cell growth and proliferation after 48 h of incubation on hybrid TNTs/ZrO2 and TNTs/V2O5 surfaces was evaluated in comparison to the uncoated TNTs of each diameter. The density of viable MG-63 cells was assessed for all the TNT surfaces, along with the cell morphology and the spreading behavior (i.e., the cell length). The ultrathin coatings retained the original morphology of the TNTs but changed the surface chemical composition, wettability, and cell behavior, whose interplay is the subject of the present investigation. These findings offer interesting views on the influence of the composition of biomedical implant surfaces, triggered by ALD ultrathin coatings on them. The outcomes of this work shed light on the assessment of the biocompatibility of the two different ALD coatings.
Keywords: povrchové vlastnosti; Cell Line; sloučeniny vanadu; Electrodes; Cell Proliferation; TiO2 nanotube layers; osteoblasty; MG-63; titan; Titanium; Osteoblasts; ZrO2, V2O5; Nanotubes; elektrody; Zirconium; Vanadium Compounds; biokompatibilní potahované materiály; nanotrubičky; Coated Materials, Biocompatible; lidé; Humans; Surface Properties; zirkonium; buněčné linie; proliferace buněk; cell viability.; atomic layer deposition